1982
DOI: 10.1246/bcsj.55.527
|View full text |Cite
|
Sign up to set email alerts
|

Collins Oxidation of Methyl (+)-13β-Abiet-8-en-18-oate and Absolute Configuration of Suaveolic Acid

Abstract: The oxidation of methyl (+)-13β-abiet-8-en-18-oate with Collins reagent yielded nine oxidation products. Their structures were elucidated on the basis of spectroscopic and chemical data to be methyl (−)-14-hydroxy-7-oxoabieta-8,11,13-trien-18-oate (1% yield), methyl (−)-11,14-dioxoabieta-8,12-dien-18-oate (1%), methyl (+)-11-oxo-13β-abiet-8-en-18-oate (18%), methyl (−)-8α,9α-epoxy-7-oxo-13β-abietan-18-oate (2%), methyl (+)-7-oxoabieta-8,11,13-trien-18-oate (2%), methyl (+)-11,14-dihydroxy-7-oxoabieta-8,11,13-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

1986
1986
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Syntheses of O-Benzyltopsentin (16), O-Benzylisotopsentin (17), , '-Dibenzylhydroxytopsentin (18), and Deoxytopsentin (6). A.…”
Section: Conversion Of Bromotopsentin (2) To Topsentin (1)mentioning
confidence: 99%
See 3 more Smart Citations
“…Syntheses of O-Benzyltopsentin (16), O-Benzylisotopsentin (17), , '-Dibenzylhydroxytopsentin (18), and Deoxytopsentin (6). A.…”
Section: Conversion Of Bromotopsentin (2) To Topsentin (1)mentioning
confidence: 99%
“…Hydrogen sulfide gas was bubbled through the solution for 5 min. CIS, 50 g; Me0H-H20, 3:1 -4:1) and HPLC (Alltech CIS, Me0H-H20, 7:3) gave 16 (7.9 mg, 0.018 mmol), 17 (5.9 mg, 0.014 mmol), 18 (1.6 mg, 0.003 mmol), and 6 (22.0 mg, 0.068 mmol) with recovered 12 (59.0 mg, 0.34 mmol) and 13 (22.8 mg, 0.081 mmol).…”
Section: Conversion Of Bromotopsentin (2) To Topsentin (1)mentioning
confidence: 99%
See 2 more Smart Citations
“…They observed no activities of suaveolic acid against human oral carcinoma, human breast cancer, and human lung cancer cells. Grassi et al [ 24 ] reported the anti-inflammatory activity of methyl suaveolate, a synthesized product of suaveolic acid [ 15 , 25 ]. However, there have been no reports about the phytotoxic activity of suaveolic acid.…”
Section: Resultsmentioning
confidence: 99%